Disseminated Scedosporium prolificans infection in an 'extensive metaboliser': navigating the minefield of drug interactions and pharmacogenomics. Issue 9 (24th April 2014) - Trubiano, J. A.; Paratz, E.; Wolf, M.; Teh, B. W.; Todaro, M.; Thursky, K. A.; Slavin, M. A.
Summary We report a case of non‐fatal disseminated Scedosporium prolificans infection, including central nervous system disease and endophthalmitis, in a relapsed acute myeloid leukaemia patient with extensive CYP2C19 metabolism. Successful treatment required aggressive surgical debridement, three times daily voriconazole dosing and cimetidine CYP2C19 inhibition. In addition, the unique use of miltefosine was employed due to azole‐chemotherapeutic drug interactions. Prolonged survival following disseminated S. prolificans, adjunctive miltefosine and augmentation of voriconazole exposure with cimetidine CYP2C19 inhibition has not been reported.